Mitochondrial DNA haplogroups J and K are not protective for Parkinson's disease in the Australian community - Mehta, Prachi; Mellick, George D.; Rowe, Dominic B.; Halliday, Glenda M.; Jones, Michael M.; Manwaring, Neil; Vandebona, Himesha; Silburn, Peter A.; Wang, Jie Jin; Mitchell, Paul; Sue, Carolyn M. (Movement disorders, 2009)
MtDNA haplogroups J and K have been associated with a decreased risk of developing Parkinson's disease (PD). To confirm this finding, we compared the distribution of mtDNA haplogroups J and K in a large sample of Australian patients with PD (n = 890) to population‐based controls (n = 3,491). We assigned subjects to haplogroups J or K using standard PCR/RFLP techniques. Of the 890 subjects with PD, 10.6% were haplogroup J (95% CI 8.6–12.8, n = 94) and 7.1% were haplogroup K (95% CI 5.5–8.9, n = 63). In our controls, 10.2% belonged to haplogroup J (95% CI 9.2–11.2, n = 356), and 7.8% were in haplogroup K (95% CI 6.9–8.7, n = 272). There was no significant difference in the prevalence of mtDNA haplogroup J or K in PD patients compared to population‐based controls. Our findings indicate that mtDNA haplogroups J and K are not associated with a lower risk of PD. © 2008 Movement Disorder Society